ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH UNTUK MENGGUNAKAN ATM PADA PT. BANK NEGARA INDONESIA (BNI) 46 Tbk KANTOR KAS MUARA BULIAN - Niki Kosasih (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The purpose of this research is to analyze the factors that influence the interest of customers to use ATM at PT. Bank Negara Indonesia (BNI) 46 tbk Cashier Office of Muara Bulian. The technique used to analyze the research data is descriptive analysis method that is reveal the condition of findings on the object of research both in the form of qualitative and quantitative data. The result of the research is obtained that the factors that influence the interest of customers to use ATM at PT. Bank Negara Indonesia (BNI) 46 tbk Cash Office Muara Bulian consists of several factors, namely technology factor, area factor, facility factor, account factor, location factor, ATM number factor and tariff factor. Of the factors that exist there are 3 (three) factors that have significant influence is the technological factor of 4.78, facilities factor of 4.68, and the location factor of 4.66.Keyword: (customer interest, technology factor, facility factor and location factor).